Ocular infection and immunity (with 916 illustrations) (Mosby, 1995)
Infection and infammation are among the leading causes of ocular morbility and blindness. In the developing world, tracoma and onchocerciasis continue to blind millions of individuals, as they have done for thousands of years. The book includes a comprehensive review of all aspects of a disease. The book begins with a two-chapter introduction that describes the history of infectious and inflammatory of diseases of the eye, and how the current state of knowledge about these disciplines was achieved. The next two sections are devoted to the latest scientific knowledge about disease mechanisms and the unique anatomic and physiological features of the eye; this background can be applied to understanding the clinical aspects of diseases. A brief third section, dealing with immonodeficiency disorders, illustrates the interface between clinical immunology and the study of infectious diseases